Is red blood cell distribution width a prognostic factor for colorectal cancer? A meta-analysis - Wen, Ze-Lin; Zhou, Xiong; Xiao, Da-Chun (Frontiers in Surgery, 2022)
The aim of the current study was to analyze whether red blood cell distribution width (RDW) was a prognostic factor for colorectal cancer (CRC) patients who underwent radical surgery. We conducted the searching strategy in three databases including the PubMed, Embase and Cochrane Library from inception to May 07, 2022, to find eligible studies. In this meta-analysis, we focused on the prognosis. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated for overall survival (OS), disease-free survival (DFS) and cancer-specific survival (CSS). A total of seven studies involving 7541 patients were included in this meta-analysis. After pooling up the HRs, RDW-CV was not an independent prognostic factor of OS (HR=1.48, I2=90%, 95% CI=0.93 to 2.36, P=0.10), however, RDW-SD was an independent prognostic factor of OS (HR=1.99, I2=0%, 95% CI=1.59 to 2.49, P<0.01). As for DFS, we found that RDW-CV (HR=1.51, I2=83%, 95% CI=0.94 to 2.43, P=0.09<0.10) and RDW-SD (HR=1.77, I2=56%, 95% CI=0.91 to 3.43, P=0.09<0.10) were both independent prognostic factors. In terms of CSS, we found that RDW-CV was not an independent prognostic factor (HR=1.23, I2=95%, 95% CI=0.72 to 2.10, P=0.46). RDW-SD was an independent prognostic factor of OS and DFS, and RDW-CV was an independent prognostic factor of DFS.